PETG sheet and preparation method thereof
By using toughening crosslinking agents in PETG sheets to form a three-dimensional crosslinking network, the problem of insufficient hygroscopicity and thermal deformation of PETG sheets is solved, efficient water molecule barrier and thermal stability are achieved, and PETG sheets are satisfied at high temperatures Application requirements in the environment.
Patent Information
- Application Number
- CN202411471357.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-22
AI Technical Summary
PETG sheets have strong hygroscopicity during processing and lack thermal deformation ability in high temperature environments, resulting in silver marks, discoloration, bubbles or cracks easily after processing and forming.
30-40 parts of PETG, 5-10 parts of acrylonitrile-butadiene-styrene copolymer, 10-15 parts of polyethylene terephthalate, 0.5-1 part of toughening crosslinking agent, and chain extender are used. A combination of 1-3 parts, 1-5 parts of pentaerythritol stearate, 60-100 parts of inorganic filler, 1-1.5 parts of aluminate coupling agent and 0.5-1.0 parts of antioxidant, through copolymerization and stirring, etc. Prepare toughened crosslinking agents to form a three-dimensional crosslinking network to reduce water molecules adsorption and improve material density.
It effectively reduces the hygroscopicity of PETG sheets, improves its bending, tensile and processing properties, ensures long-term use in high-temperature environments and the processing yield rate is higher than 94%, and meets industrial production requirements.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic polymer compounds, and in particular relates to a PETG plate and a preparation method thereof. Background Art
[0002] Polyvinyl chloride, or PVC for short, is widely used in food, construction, medical and daily life because of its advantages of easy processing and low cost. Its application scenarios are closely related to human life, but PVC itself will volatilize harmful substances such as vinyl chloride and dioxins that endanger human health during use, especially in direct sunlight and high temperature environments. In addition, the plasticizers, stabilizers and other additives added to PVC during the production process are difficult to separate later, making PVC difficult to recycle. Incineration for power generation will release a large amount of toxic substances. Generally, it can only be landfilled as construction waste. PVC is difficult to degrade in the landfill environment, which will occupy land resources for a long time and cause potential pollution to groundwater. Since the application scenarios of PVC are closely related to the human living environment, there is an urgent need to find a safer, more environmentally friendly and recyclable material.
[0003] Polyethylene terephthalate-1,4-cyclohexanedimethanol is an ideal material to replace PVC because of its safe and environmentally friendly production and use processes, and its ability to be recycled through simple melting and regranulation.
[0004] Polyethylene terephthalate-1,4-cyclohexanedimethanol, referred to as PETG, is a thermoplastic polyester made by copolymerizing terephthalic acid, ethylene glycol and 1,4-cyclohexanedimethanol, or by ester exchange reaction between 1,4-cyclohexanedimethanol and ethylene terephthalate. The addition of 1,4-cyclohexanedimethanol as a comonomer reduces the regularity of the polyester chain and the crystallinity, making PETG more inclined to form an amorphous structure. Compared with ordinary polyethylene terephthalate, PETG has superior performance in terms of transparency, toughness, processing performance and environmental protection. These characteristics make PETG widely used in many fields such as food and cosmetics packaging, medical treatment, and building decoration.
[0005] However, there are also some problems with the PETG obtained by the prior art. For example, the humidity requirement of the PETG material is relatively high during the processing. This is because PETG, as a polyester material, contains a large number of hydrophilic groups (such as hydroxyl groups) on its molecular chain. These groups have affinity for water molecules, making PETG easy to absorb and retain moisture; PETG is an amorphous structure at the same time, and its molecular chain arrangement is relatively disordered, and it is impossible to form a dense crystal structure to effectively block the invasion of moisture. Therefore, water molecules are more likely to penetrate into the inside of the PETG material. And the auxiliary materials added during the processing often contain moisture, which will cause the problems such as silver streaks, discoloration, bubbles or cracks to easily occur after the PETG is processed and formed. In addition, a certain amount of flexible segments are contained in the PETG molecular chain, and these flexible segments move more aggravated when heated, and are more likely to slide, bend and stretch relatively, resulting in a relatively low thermal deformation temperature of the PETG material.
[0006] Therefore, for those skilled in the art, how to reduce the hygroscopicity of PETG during processing and improve the thermal deformation of PETG under high temperature environment is the key to promoting the large-scale replacement of PVC by PETG.
[0007] Chinese patent CN111334008A discloses a PETG antibacterial sheet and a preparation method thereof, wherein the PETG antibacterial sheet is prepared using PETG resin, an antibacterial agent and a silane coupling agent as raw materials, and the preparation method comprises the following steps: firstly mixing the antibacterial agent and the silane coupling agent in proportion and stirring for 10-60 minutes; then adding the PETG resin in proportion and stirring again for 30-60 minutes; feeding the mixed raw materials into a sheet production line by a screw feeder for processing to obtain a PETG sheet; and finally subjecting the PETG sheet to a high temperature and high pressure treatment to obtain the PETG antibacterial sheet.
[0008] This patent has the following disadvantages: the addition of silane coupling agent in this patent is mainly to bridge the PETG resin and the antibacterial agent to improve the antibacterial effect of the PETG resin; but the patent does not explicitly mention that the patent has the purpose of improving the thermal deformation of PETG under high temperature environment, and the raw materials and processing process used do not have the effect of significantly improving the thermal deformation.
[0009] Chinese patent CN112831162A discloses a weather-resistant and corrosion-resistant PETG sheet and a preparation method thereof. The PETG sheet is mainly made of the following raw materials in parts by weight: 80-100 parts of PETG resin, 20-30 parts of PET resin, 10-20 parts of melamine cyanurate, 2-8 parts of sodium antimonate, 5-10 parts of ethylene-octene copolymer, 0.2-0.8 parts of oxidized polyethylene wax, and 2-8 parts of hindered phenol antioxidant 1098.
[0010] The patent has the following shortcomings: the PET resin in the patent is mainly used to assist the PETG resin to improve the heat resistance, chemical resistance and mechanical strength of the board; melamine cyanurate and sodium antimonate mainly play a flame retardant effect; ethylene-octene copolymer mainly improves thermal deformation and improves the low-temperature impact resistance of the board; oxidized polyethylene wax is used as a lubricant to reduce resistance and make the added raw materials easy to process. Therefore, the patent does not mention the improvement of the drying process during the processing, and the added components do not have the function of significantly improving the hygroscopicity of the board. Summary of the invention
[0011] The object of the present invention is to provide a PETG sheet to solve the problems in the current preparation method that the PETG sheet has strong hygroscopicity during processing and the PETG sheet has insufficient ability to resist thermal deformation; the present invention also provides a preparation method.
[0012] To achieve the above object, the technical solution adopted by the present invention is:
[0013] The PETG plate of the present invention is prepared from the following components in parts by mass: 30-40 parts of PETG, 5-10 parts of acrylonitrile-butadiene-styrene copolymer, 10-15 parts of polyethylene terephthalate, 0.5-1 parts of a toughening cross-linking agent, 1-3 parts of a chain extender, 1-5 parts of pentaerythritol stearate, 60-100 parts of an inorganic filler, 1-1.5 parts of an aluminate coupling agent and 0.5-1.0 parts of an antioxidant; wherein the toughening cross-linking agent is prepared by copolymerization of 2-cyclohexyl acrylate, maleic anhydride and butyl acrylate.
[0014] Acrylonitrile-butadiene-styrene copolymer is referred to as ABS; polyethylene terephthalate is referred to as PET; pentaerythritol stearate is referred to as PETS.
[0015] in:
[0016] The copolymerization reaction temperature is 65-75° C., and the copolymerization reaction time is 25-40 minutes.
[0017] The mass ratio of 2-cyclohexyl acrylate, maleic anhydride and butyl acrylate is 1:0.4:0.5-0.8.
[0018] An auxiliary reactant is added into the copolymerization reaction.
[0019] The auxiliary reaction agent includes mercaptopropionic acid, azobisisobutyronitrile and tetrahydrofuran.
[0020] The amount of mercaptopropionic acid added is 0.3-0.6% of the mass of the toughening crosslinking agent; the amount of azobisisobutyronitrile added is 1-1.5% of the mass of the toughening crosslinking agent; and the amount of tetrahydrofuran added is 95-100% of the mass of maleic anhydride.
[0021] The PETG is one or both of PN200 and GN071; the acrylonitrile-butadiene-styrene copolymer is one or both of SD-0190H and GP-22; the polyethylene terephthalate is one or both of CR8816 and CR8828; the chain extender is one or both of ADR-4468 and ADR-4370; the inorganic filler is one or more of 1250 mesh calcium carbonate, 1000 mesh montmorillonite and 2000 mesh wollastonite; the antioxidant is one or both of antioxidant 5057 and antioxidant 1135.
[0022] The method for preparing the PETG sheet of the present invention comprises the following steps:
[0023] (1) preparing a toughening cross-linking agent for standby use;
[0024] (2) stirring the inorganic filler and the aluminate coupling agent once, and obtaining a modified inorganic filler after the stirring is completed;
[0025] (3) PETG and a chain extender are pre-mixed, and then acrylonitrile-butadiene-styrene copolymer, polyethylene terephthalate, toughening cross-linking agent, pentaerythritol stearate, modified inorganic filler and antioxidant are added thereto for secondary stirring;
[0026] (4) After the secondary stirring is completed, the PETG sheet is obtained by extrusion, calendering and leveling.
[0027] in:
[0028] The primary stirring temperature is 100-110° C., and the primary stirring time is 10-15 minutes; the premixing temperature is 65-75° C.; the secondary stirring temperature is 40-60° C., and the secondary stirring time is 15-25 minutes.
[0029] The extrusion adopts a twin-screw extruder, the barrel temperature of the twin-screw extruder is 195-220°C, and the head temperature is 210-230°C; the calendering and shaping adopts a three-roll calender, the three-roll calender comprises an upper roller, a middle roller and a lower roller, the upper roller temperature is 90-100°C, the middle roller temperature is 80-90°C, and the lower roller temperature is 70-85°C.
[0030] Azobisisobutyronitrile is used as a free radical initiator; in the copolymerization reaction, it can decompose under heating conditions to produce free radicals, thereby initiating the copolymerization of 2-cyclohexyl acrylate, maleic anhydride and butyl acrylate. Mercaptopropionic acid is used as a chain transfer agent or reaction regulator; in the copolymerization reaction, it can terminate the chain growth by capturing free radicals. By adding an appropriate amount of mercaptopropionic acid, the chain growth can be terminated in time to obtain the desired polymer molecular weight. Tetrahydrofuran is used as a solvent to help disperse the reactants, thereby improving the efficiency of the copolymerization reaction.
[0031] The beneficial effects of the present invention are as follows:
[0032] (1) Premix the chain extender with PETG. Since the chain extender contains active functional groups (such as epoxy groups), it will react with the hydroxyl and carboxyl groups at the ends of the PETG molecular chains to form stable covalent bonds, so that the PETG molecular chains grow to form PETG extended molecular chains, giving the PETG molecular chains more active sites. Then add the toughening cross-linking agent to the extended PETG. Each toughening cross-linking agent molecule contains multiple active sites, which can react with the hydroxyl and carboxyl groups on multiple PETG extended molecular chains through condensation polymerization, addition, etc. to form a three-dimensional cross-linking network, thereby effectively shielding the hydrophilic groups (such as hydroxyl and carboxyl groups) on the PETG molecular chains and reducing the adsorption of water molecules. At the same time, it also improves the density of the system and reduces the penetration of water molecules, thereby effectively overcoming the problem of high hygroscopicity during the processing of PETG.
[0033] By first adding the chain extender, the chain extender has increased the length of the PETG molecular chain, and the toughening cross-linking agent further connects these PETG molecular chains tightly together through cross-linking. This method of adding in sequence can prevent excessive cross-linking and form a more uniform and stable three-dimensional cross-linked network, which effectively improves the bending and tensile properties; prevents the three-dimensional cross-linked network from being too dense due to excessive cross-linking, at which time the molecular chains will be difficult to slide and stretch, resulting in poor toughness and processing performance, and even local stress cannot be further transmitted and concentrated, causing local brittle fracture of the PETG sheet.
[0034] (2) A three-dimensional cross-linking network is formed between the toughening cross-linking agent and the PETG molecules. When the material is subjected to external force, the three-dimensional cross-linking network can absorb and disperse part of the energy, thereby slowing down the expansion of cracks and surface cracking. The toughening cross-linking agent not only reacts with the PETG molecular chain, but the active groups on the toughening cross-linking agent, such as the ester group, can also react with the hydroxyl groups on the aluminate coupling agent to form covalent bonds through addition reactions. The toughening cross-linking agent can then bridge the PETG and the inorganic filler modified by the aluminate coupling agent to form a cross-linking system.
[0035] This bridging effect can enhance the dispersibility of inorganic filler particles in the three-dimensional cross-linked network. This good dispersibility not only helps to utilize the interface slip and particle fracture mechanisms on the surface of inorganic filler particles to reduce stress concentration points in composite materials, limit crack expansion, and improve the bending, tensile and processing properties of materials; at the same time, uniform and well-dispersed inorganic fillers can also act as heterogeneous nucleating agents to increase the order of PETG molecular chains on their surfaces and make the PETG molecules more closely arranged. On the one hand, a higher order reduces the free volume and limits the thermal motion of the molecular chains; on the other hand, a higher order provides a better thermal conductivity path, thereby reducing the risk of deformation of PETG sheets due to local heat accumulation.
[0036] (3) The toughening crosslinking agent prepared by the reaction of 2-cyclohexyl acrylate, maleic anhydride and butyl acrylate has a polarity very close to that of PETG. Therefore, compared with the existing commercially available crosslinking agents, it has better compatibility with PETG and can form a more uniform mixed system. Among them, butyl acrylate contains a straight alkyl chain with a low rotation barrier, which makes the molecular chain easier to bend and deform. This flexibility makes the molecular morphology of the toughening crosslinking agent more flexible, which helps to form a three-dimensional network structure with a lower potential energy state. At this time, the three-dimensional network structure is more stable and denser; the cyclohexyl structure in the 2-cyclohexyl acrylate molecule is relatively rigid, which supplements the rigidity of the segment part that bears the bridging function, thereby improving the overall rigidity of the crosslinking system; maleic anhydride contains an unsaturated carbon-carbon double bond and a five-membered cyclic anhydride structure, so it can react with 2-cyclohexyl acrylate or butyl acrylate to optimize the length, conformation and crosslinking active site distribution of the toughening crosslinking agent molecule, thereby improving the crosslinking reaction efficiency and the mechanical properties of the crosslinking network.
[0037] (4) The oxygen atom in the anhydride group (CO-O-CO) of maleic anhydride has a high electronegativity and can form a hydrogen bond network with polar groups such as hydroxyl and carboxyl groups in the PETG molecular chain. Since the PETG molecular chain is relatively flexible and easily entangled, it will cause hydroxyl shielding and affect the cross-linking efficiency. The action distance of hydrogen bonds is very short. The existence of the hydrogen bond network can promote the stretching of the molecular chain, overcome the entanglement phenomenon, and thus improve the cross-linking efficiency.
[0038] (5) Finally, the raw materials of the present invention are relatively easy to obtain and process. The PETG sheet produced by the present invention has been tested to have a tensile strength of >30MPa, a flexural strength of >50MPa, a flexural modulus of >8500MPa, a processing yield of >94%, and can be used for a long time in a high temperature environment for 36 months. DETAILED DESCRIPTION
[0039] The present invention is specifically described and illustrated below in conjunction with embodiments.
[0040] Example 1
[0041] PETG, brand PN200, produced by SK Chemical of South Korea; ABS, brand SD-0190H, produced by Lotte Chemical of South Korea; PET, brand CR8816, produced by China Resources Polyester (Changzhou) Co., Ltd.; PETS, brand PETS-4, produced by Shandong Ruijie New Materials Co., Ltd.; chain extender, brand ADR-4468, produced by BASF of Germany; aluminate coupling agent, brand DL-411, produced by Shandong Shoucheng Chemical Co., Ltd.; antioxidant, model antioxidant 5057, produced by Dongguan Guangsiyuan Polyurethane Materials Co., Ltd. Prepare the raw materials according to the above brands: PETG 300kg, ABS 70kg, PET 100kg, toughening crosslinking agent 8kg, chain extender 20kg, PETS 20kg, 1250 mesh calcium carbonate 900kg, aluminate coupling agent 10kg and antioxidant 5kg.
[0042] The toughening cross-linking agent needs to be prepared before use.
[0043] Preparation of toughening crosslinking agent: pre-purge the reactor with nitrogen for 5 minutes, and then continue to fill nitrogen to 1.2MPa; add 40kg maleic anhydride, 38.4kg tetrahydrofuran and 0.95kg mercaptopropionic acid to the reactor, open the steam jacket, heat the reactor to 70°C and start stirring the reactor; connect 100kg 2-cyclohexyl acrylate, 50kg butyl acrylate and 2.37kg azobisisobutyronitrile to a peristaltic pump, and pump them into the reactor at a rate of 2.5kg / min in sequence. After the pumping is completed, continue to stir the copolymerization reaction for 30 minutes; after the reaction is completed, filter it through a filter press first, and then enter a rake vacuum dryer, set the working pressure of the rake vacuum dryer to -0.01MPa, the temperature to 60°C, and the speed to 15rpm, vacuum dry for 12h, and obtain a powdered toughening crosslinking agent at the outlet of the rake vacuum dryer, which is stored in a dry place away from light. Take 8kg of toughening crosslinking agent for use.
[0044] 1250 mesh calcium carbonate and aluminate coupling agent were blended and stirred at 110° C. for 10 minutes to obtain a modified inorganic filler.
[0045] PETG and chain extender were premixed at 65°C for 18 minutes, and then ABS, PET, toughening crosslinking agent, PETS, modified inorganic filler and antioxidant were added and stirred at 40°C for 25 minutes. After stirring, the mixture entered into a twin-screw extruder, wherein the barrel temperature of the extruder was 210°C, and the head temperature was 220°C. After extrusion by the twin-screw extruder, the mixture entered into a three-roll calender, and the upper roll temperature, the middle roll temperature, and the lower roll temperature were set to 95°C, 85°C, and 75°C, and the mixture was calendered and shaped by the three-roll calender, and finally entered into a leveling machine for leveling and burr removal, and finally a PETG sheet was obtained.
[0046] Example 2
[0047] PETG, brand GN071, produced by Eastman Chemical of the United States; ABS, brand GP-22, produced by BASF of Germany; PET, brand CR8828, produced by China Resources Polyester (Changzhou) Co., Ltd.; PETS, brand PETS-4, produced by Shandong Ruijie New Materials Co., Ltd.; chain extender, brand ADR-4370, produced by BASF of Germany; aluminate coupling agent, brand DL-411, produced by Shandong Shoucheng Chemical Co., Ltd.; antioxidant, model antioxidant 1135, produced by Changzhou Xince Polymer Materials Co., Ltd. Prepare the raw materials according to the above brands: PETG 400kg, ABS 100kg, PET 150kg, toughening crosslinking agent 10kg, chain extender 30kg, PETS 10kg, 1000 mesh montmorillonite 200kg, 2000 mesh wollastonite 400kg, aluminate coupling agent 12kg and antioxidant 8kg.
[0048] The toughening cross-linking agent needs to be prepared before use.
[0049] Preparation of toughening crosslinking agent: pre-purge the reactor with nitrogen for 5 minutes, and then continue to fill nitrogen to 1.2MPa; add 40kg maleic anhydride, 40kg tetrahydrofuran and 1.2kg mercaptopropionic acid to the reactor, open the steam jacket, heat the reactor to 75°C and start stirring the reactor; connect 100kg 2-cyclohexyl acrylate, 70kg butyl acrylate and 2.4kg azobisisobutyronitrile to the peristaltic pump, and pump them into the reactor at a rate of 2.5kg / min in turn. After the pumping is completed, continue to stir the copolymerization reaction for 25 minutes; after the reaction is completed, filter it through a filter press first, and then enter the rake vacuum dryer, set the working pressure of the rake vacuum dryer to -0.02MPa, the temperature to 60°C, and the speed to 15rpm, vacuum dry for 12h, and obtain a powdered toughening crosslinking agent at the outlet of the rake vacuum dryer, label it, and store it in a dry place away from light. Take 10kg of toughening crosslinking agent for use.
[0050] 1000 mesh calcium carbonate, 2000 mesh wollastonite and an aluminate coupling agent were mixed and stirred at 105° C. for 12 minutes to obtain a modified inorganic filler.
[0051] PETG and chain extender were premixed at 75°C for 10 minutes, and then ABS, PET, toughening crosslinking agent, PETS, modified inorganic filler and antioxidant were added and stirred at 50°C for 20 minutes. After stirring, the mixture entered into a twin-screw extruder, wherein the extruder barrel temperature was 195°C, and the die head temperature was 210°C. After extrusion by the twin-screw extruder, the mixture entered into a three-roll calender, and the upper roll temperature, the middle roll temperature, and the lower roll temperature were set to 100°C, 90°C, and 85°C, and the mixture was calendered and shaped by the three-roll calender, and finally entered into a leveling machine for leveling and burr removal, and finally a PETG sheet was obtained.
[0052] Example 3
[0053] PETG, brand GN071, produced by Eastman Chemical of the United States; ABS, brand SD-0190H, produced by Lotte Chemical of South Korea; PET, brand CR8828, produced by China Resources Polyester (Changzhou) Co., Ltd.; PETS, brand PETS-4, produced by Shandong Ruijie New Materials Co., Ltd.; chain extender, brand ADR-4370, produced by BASF of Germany; aluminate coupling agent, brand DL-411, produced by Shandong Shoucheng Chemical Co., Ltd.; antioxidant, model antioxidant 5057, produced by Dongguan Guangsiyuan Polyurethane Materials Co., Ltd. According to the above brands, the raw materials are prepared: 350kg of PETG, 50kg of ABS, 120kg of PET, 5kg of toughening crosslinking agent, 10kg of chain extender, 50kg of PETS, 1000kg of 2000 mesh wollastonite, 15kg of aluminate coupling agent and 10kg of antioxidant.
[0054] The toughening cross-linking agent needs to be prepared before use.
[0055] Preparation of toughening crosslinking agent: pre-purge the reactor with nitrogen for 5 minutes, and then continue to fill nitrogen to 1.2MPa; add 40kg maleic anhydride, 40kg tetrahydrofuran and 0.66kg mercaptopropionic acid to the reactor, open the steam jacket, heat the reactor to 65°C and start stirring the reactor; connect 100kg 2-cyclohexyl acrylate, 80kg butyl acrylate and 2.42kg azobisisobutyronitrile to a peristaltic pump, and pump them into the reactor at a rate of 2.5kg / min in sequence. After the pumping is completed, continue to stir the copolymerization reaction for 40 minutes; after the reaction is completed, filter it through a filter press first, and then enter a rake vacuum dryer, set the working pressure of the rake vacuum dryer to -0.02MPa, the temperature to 60°C, and the speed to 20rpm, vacuum dry for 12h, and obtain a powdered toughening crosslinking agent at the outlet of the rake vacuum dryer, which is stored in a dry place away from light. Take 5kg of toughening crosslinking agent for use.
[0056] 2000 mesh wollastonite and aluminate coupling agent were blended and stirred at 100° C. for 15 minutes to obtain a modified inorganic filler.
[0057] PETG and chain extender were premixed at 70°C for 10 minutes, and then ABS, PET, toughening crosslinking agent, PETS, modified inorganic filler and antioxidant were added and stirred at 60°C for 15 minutes. After stirring, the mixture entered into a twin-screw extruder, wherein the extruder barrel temperature was 220°C, and the die head temperature was 230°C. After extrusion by the twin-screw extruder, the mixture entered into a three-roll calender, and the upper roll temperature, the middle roll temperature, and the lower roll temperature were set to 90°C, 80°C, and 70°C, and the mixture was calendered and shaped by the three-roll calender, and finally entered into a leveling machine for leveling and burr removal, and finally a PETG sheet was obtained.
[0058] Example 4
[0059] PETG, brand PN200, produced by SK Chemicals of South Korea; ABS, brand SD-0190H, produced by Lotte Chemicals of South Korea; PET, brand CR8816, produced by China Resources Polyester (Changzhou) Co., Ltd.; PETS, brand PETS-4, produced by Shandong Ruijie New Materials Co., Ltd.; chain extender, brand ADR-4468, produced by BASF of Germany; aluminate coupling agent, brand DL-411, produced by Shandong Shoucheng Chemical Co., Ltd.; antioxidant, model antioxidant 5057, produced by Dongguan Guangsiyuan Polyurethane Materials Co., Ltd. Prepare the raw materials according to the above brands: prepare 300kg of PETG, 70kg of ABS, 100kg of PET, 8kg of toughening crosslinking agent, 20kg of chain extender, 20kg of PETS, 900kg of 1250 mesh calcium carbonate, 10kg of aluminate coupling agent and 5kg of antioxidant.
[0060] The toughening cross-linking agent needs to be prepared before use.
[0061] Preparation of toughening crosslinking agent: pre-purge the reactor with nitrogen for 5 minutes, and then continue to fill nitrogen to 1.2MPa; add 80kg maleic anhydride, 80kg tetrahydrofuran, and 1.32kg mercaptopropionic acid to the reactor, open the steam jacket of the reactor, heat the reactor to 70°C and start stirring the reactor; connect 200kg 2-cyclohexyl acrylate, 160kg butyl acrylate and 4.4kg azobisisobutyronitrile to a peristaltic pump, and pump them into the reactor at a rate of 2.5kg / min in sequence. After the pumping is completed, continue to stir and copolymerize for 30 minutes; after the reaction is completed, first enter the rotary evaporator and rotary evaporate at 35°C for 20 minutes; then enter the rake vacuum dryer, set the working pressure of the rake vacuum dryer to -0.02MPa, the temperature to 60°C, and the speed to 15rpm, vacuum dry for 12 hours, and obtain a powdered toughening crosslinking agent at the outlet of the rake vacuum dryer, which is stored in a dry place away from light. Take 8kg of toughening crosslinking agent for use.
[0062] 1250 mesh calcium carbonate and aluminate coupling agent were blended and stirred at 110° C. for 10 minutes to obtain a modified inorganic filler.
[0063] PETG and chain extender were premixed at 65°C for 18 minutes, and then ABS, PET, toughening crosslinking agent, PETS, modified inorganic filler and antioxidant were added and stirred at 50°C for 25 minutes. After stirring, the mixture entered into a twin-screw extruder, wherein the extruder barrel temperature was 220°C, and the die head temperature was 230°C. After extrusion by the twin-screw extruder, the mixture entered into a three-roll calender, and the upper roll temperature, the middle roll temperature, and the lower roll temperature were set to 90°C, 85°C, and 70°C, and the mixture was calendered and shaped by the three-roll calender, and finally entered into a leveling machine for leveling and burr removal, and finally a PETG sheet was obtained.
[0064] Example 5
[0065] PETG, brand GN071, produced by Eastman Chemical of the United States; ABS, brand GP-22, produced by BASF of Germany; PET, brand CR8828, produced by China Resources Polyester (Changzhou) Co., Ltd.; PETS, brand PETS-4, produced by Shandong Ruijie New Materials Co., Ltd.; chain extender, brand ADR-4370, produced by BASF of Germany; aluminate coupling agent, brand DL-411, produced by Shandong Shoucheng Chemical Co., Ltd.; antioxidant, model antioxidant 1135, produced by Changzhou Xince Polymer Materials Co., Ltd. Prepare the raw materials according to the above brands: PETG 350kg, ABS 100kg, PET 150kg, toughening crosslinking agent 8kg, chain extender 10kg, PETS 50kg, 1250 mesh calcium carbonate 800kg, 2000 mesh wollastonite 200kg, aluminate coupling agent 15kg and antioxidant 5kg.
[0066] The toughening cross-linking agent needs to be prepared before use.
[0067] Preparation of toughening crosslinking agent: pre-purge the reactor with nitrogen for 5 minutes, and then continue to fill nitrogen to 1.2MPa; add 80kg maleic anhydride, 76kg tetrahydrofuran, and 1.52kg mercaptopropionic acid to the reactor, open the steam jacket of the reactor, heat the reactor to 70°C and start stirring the reactor; connect 200kg 2-cyclohexyl acrylate, 100kg butyl acrylate and 4.56kg azobisisobutyronitrile to a peristaltic pump, and pump them into the reactor at a rate of 2.5kg / min in sequence. After the pumping is completed, continue to stir and copolymerize for 30 minutes; after the reaction is completed, first enter the rotary evaporator and rotary evaporate at 35°C for 25 minutes; then enter the rake vacuum dryer, set the working pressure of the rake vacuum dryer to -0.02MPa, the temperature to 60°C, and the speed to 15rpm, vacuum dry for 12 hours, and obtain a powdered toughening crosslinking agent at the outlet of the rake vacuum dryer, which is stored in a dry place away from light. Take 8kg of toughening crosslinking agent for use.
[0068] 1250 mesh calcium carbonate, 2000 mesh wollastonite and aluminate coupling agent were mixed and stirred at 105° C. for 15 minutes to obtain a modified inorganic filler.
[0069] PETG and chain extender were premixed at 65°C for 18 minutes, and then ABS, PET, toughening crosslinking agent, PETS, modified inorganic filler and antioxidant were added and stirred at 40°C for 25 minutes. After stirring, the mixture entered into a twin-screw extruder, wherein the extruder barrel temperature was 215°C, and the die head temperature was 225°C. After extrusion by the twin-screw extruder, the mixture entered into a three-roll calender, and the upper roll temperature, the middle roll temperature, and the lower roll temperature were set to 100°C, 90°C, and 85°C, and the mixture was calendered and shaped by the three-roll calender, and finally entered into a leveling machine for leveling and burr removal, and finally a PETG sheet was obtained.
[0070] Example 6
[0071] PETG, brand PN200, produced by SK Chemicals of South Korea; ABS, brand GP-22, produced by BASF of Germany; PET, brand CR8816, produced by China Resources Polyester (Changzhou) Co., Ltd.; PETS, brand PETS-4, produced by Shandong Ruijie New Materials Co., Ltd.; chain extender, brand ADR-4468, produced by BASF of Germany; aluminate coupling agent, brand DL-411, produced by Shandong Shoucheng Chemical Co., Ltd.; antioxidant, model antioxidant 1135, produced by Changzhou Xince Polymer Materials Co., Ltd. Prepare the raw materials according to the above brands: PETG 350kg, ABS 50kg, PET 150kg, toughening crosslinking agent 10kg, chain extender 30kg, PETS 10kg, 1000 mesh montmorillonite 600kg, aluminate coupling agent 12kg and antioxidant 10kg.
[0072] The toughening cross-linking agent needs to be prepared before use.
[0073] Preparation of toughening crosslinking agent: pre-purging the reactor with nitrogen for 5 minutes, and then continuing to fill nitrogen to 1.2MPa; adding 80kg of maleic anhydride, 79.2kg of tetrahydrofuran, and 2.4kg of mercaptopropionic acid to the reactor, opening the steam jacket of the reactor, heating the reactor to 70°C and starting the reactor to stir; connecting 200kg of 2-cyclohexyl acrylate, 120kg of butyl acrylate and 4.56kg of azobisisobutyronitrile to a peristaltic pump, and pumping them into the reactor at a rate of 2.5kg / min in sequence, and continuing to stir the copolymerization reaction for 40min after the pumping is completed; after the reaction is completed, first entering a rotary evaporator, and rotary evaporating at 35°C for 25min; then entering a rake vacuum dryer, setting the working pressure of the rake vacuum dryer to -0.01MPa, the temperature to 60°C, and the rotation speed to 12rpm, vacuum drying for 12h, and obtaining a powdered toughening crosslinking agent at the outlet of the rake vacuum dryer, which is stored in a dry place away from light. When using, take 10kg of toughening cross-linking agent.
[0074] 1000 mesh montmorillonite and an aluminate coupling agent were blended and stirred at 100° C. for 10 minutes to obtain a modified inorganic filler.
[0075] PETG and chain extender were premixed at 65°C for 18 minutes, and then ABS, PET, toughening crosslinking agent, PETS, modified inorganic filler and antioxidant were added and stirred at 50°C for 15 minutes. After stirring, the mixture entered into a twin-screw extruder, wherein the extruder barrel temperature was 195°C, and the die head temperature was 210°C. After extrusion by the twin-screw extruder, the mixture entered into a three-roll calender, and the upper roll temperature, the middle roll temperature, and the lower roll temperature were set to 95°C, 80°C, and 80°C, and the mixture was calendered and shaped by the three-roll calender, and finally entered into a leveling machine for leveling and burr removal, and finally a PETG sheet was obtained.
[0076] Comparative Example 1
[0077] 8 kg of toughening cross-linking agent was replaced by 8 kg of PETG. There was no need to prepare toughening cross-linking agent. The remaining steps were the same as those in Example 1.
[0078] Comparative Example 2
[0079] The chain extender, toughening cross-linking agent and other components are directly stirred without pre-mixing, and the remaining steps are the same as those in Example 1.
[0080] Comparative Example 3
[0081] Maleic anhydride was not used in the preparation of the toughening crosslinking agent, and the remaining steps were the same as those in Example 1.
[0082] Comparative Example 4
[0083] When preparing the toughening crosslinking agent, 2-cyclohexyl acrylate was not used, and the remaining steps were the same as in Example 1.
[0084] Comparative Example 5
[0085] Butyl acrylate was not used in the preparation of the toughening crosslinking agent, and the remaining steps were the same as those in Example 1.
[0086] Comparative Example 6
[0087] When preparing the toughening crosslinking agent, only maleic anhydride was used, and the remaining steps were the same as in Example 1.
[0088] Comparative Example 7
[0089] When preparing the toughening crosslinking agent, only 2-cyclohexyl acrylate was used, and the remaining steps were the same as in Example 1.
[0090] Comparative Example 8
[0091] When preparing the toughening crosslinking agent, only butyl acrylate was used, and the remaining steps were the same as in Example 1.
[0092] Use performance test:
[0093] According to the standard shown in GB / T 9341-2008, the bending strength and bending modulus of the embodiments and comparative examples were tested; according to the standard shown in GB / T 1040.1-2018, the tensile strength of the embodiments and comparative examples was tested. The specific data are shown in Table 1.
[0094] The forming yield rate is obtained by observing the surface of the plate through a magnifying glass for silver streaks, discoloration, bubbles or cracks, and then calculating the ratio of the area of the good PETG plate to the total area of the processed PETG plate to find the processing yield rate.
[0095] The plates prepared in the embodiment and the comparative example were cut into samples with a length of 1m, a width of 1m and a thickness of 5mm. The samples were placed in an aging test box, the temperature was set to 65°C, and a load of 500N / m was applied evenly. 2 Every month, the sample to be tested was taken out and placed on a bending tester, and a load of 60% of the bending strength measured in each of the embodiments and comparative examples in Table 1 was applied until the sample to be tested broke. The measurement results are shown in Table 1.
[0096]
[0097] As can be seen from Table 1, the PETG sheets prepared by the present invention (i.e., Examples 1-6) have a tensile strength of >30 MPa, a flexural strength of >50 MPa, and a flexural modulus of >8500 MPa, and have good bending and tensile properties; the processing yield rate is >94%, which shows that the present invention effectively improves the hygroscopicity of the PETG sheets during processing, and the prepared PETG sheets are basically free of silver streaks, discoloration, bubbles or cracks, and meet the requirements of industrial production; and can be used for a long time in a high temperature environment for up to 36 months, which shows that the present invention effectively improves the thermal deformation of the PETG sheets, and basically does not deform under the conditions of high temperature environment and long-term load, has a good service life, and basically meets the use requirements in the main application scenarios.
[0098] Although the present invention is described in detail in conjunction with the embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, those skilled in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions should all be within the scope of the present invention.
Claims
1. A PETG sheet, characterized in that: The invention is prepared from the following components in parts by mass: 30-40 parts of PETG, 5-10 parts of acrylonitrile-butadiene-styrene copolymer, 10-15 parts of polyethylene terephthalate, 0.5-1 parts of a toughening crosslinking agent, 1-3 parts of a chain extender, 1-5 parts of pentaerythritol stearate, 60-100 parts of an inorganic filler, 1-1.5 parts of an aluminate coupling agent and 0.5-1.0 parts of an antioxidant; wherein the toughening crosslinking agent is prepared by copolymerization of 2-cyclohexyl acrylate, maleic anhydride and butyl acrylate, and the mass ratio of 2-cyclohexyl acrylate, maleic anhydride and butyl acrylate is 1:0.4:0.5-0.8; The preparation of PETG sheet comprises the following steps: (1) preparing a toughening cross-linking agent for standby use; (2) stirring the inorganic filler and the aluminate coupling agent once, and obtaining a modified inorganic filler after the stirring is completed; (3) PETG and a chain extender are pre-mixed, and then acrylonitrile-butadiene-styrene copolymer, polyethylene terephthalate, toughening cross-linking agent, pentaerythritol stearate, modified inorganic filler and antioxidant are added thereto for secondary stirring; (4) After the secondary stirring is completed, the PETG sheet is obtained by extrusion, calendering and leveling; Among them, the pre-mixing temperature is 65-75°C; the secondary stirring temperature is 40-60°C, and the secondary stirring time is 15-25min.
2. The PETG sheet according to claim 1, characterized in that: The copolymerization reaction temperature is 65-75°C, and the copolymerization reaction time is 25-40min.
3. The PETG sheet according to claim 1, characterized in that: Auxiliary reactants are added during the copolymerization reaction.
4. The PETG sheet according to claim 3, characterized in that: Auxiliary reagents include mercaptopropionic acid, azobisisobutyronitrile and tetrahydrofuran.
5. The PETG sheet according to claim 4, characterized in that: When preparing the toughening crosslinking agent by copolymerization, the amount of mercaptopropionic acid added is 0.3-0.6% of the total mass of 2-cyclohexyl acrylate, maleic anhydride and butyl acrylate; the amount of azobisisobutyronitrile added is 1-1.5% of the total mass of 2-cyclohexyl acrylate, maleic anhydride and butyl acrylate; and the amount of tetrahydrofuran added is 95-100% of the mass of maleic anhydride.
6. The PETG sheet according to claim 1, characterized in that: PETG is one or both of PN200 and GN071; acrylonitrile-butadiene-styrene copolymer is one or both of SD-0190H and GP-22; polyethylene terephthalate is one or both of CR8816 and CR8828; chain extender is one or both of ADR-4468 and ADR-4370; inorganic filler is one or more of 1250 mesh calcium carbonate, 1000 mesh montmorillonite and 2000 mesh wollastonite; antioxidant is one or both of antioxidant 5057 and antioxidant 1135.
7. The PETG sheet according to claim 1, characterized in that: The stirring temperature is 100-110°C and the stirring time is 10-15 minutes.
8. The PETG sheet according to claim 1, characterized in that: The extrusion adopts a twin-screw extruder with a barrel temperature of 195-220°C and a head temperature of 210-230°C. The calendering and shaping adopts a three-roll calender, which includes an upper roll, a middle roll and a lower roll. The upper roll temperature is 90-100°C, the middle roll temperature is 80-90°C, and the lower roll temperature is 70-85°C.
Citation Information
Patent Citations
PETG antibacterial plate and preparation method thereof
CN111334008A
Weather-resistant and corrosion-resistant PETG plate and preparation method thereof
CN112831162A
Toughened polyethylene glycol terephthalate and preparation method thereof
CN101870803A
Preparation method of acrylic acid grafted and modified saturated polyester resin
CN105968271A